Pengaruh Kemiringan Kolektor Menggunakan Adsorben Arang Aktif Terhadap Efisiensi Kolektor Surya Pada Proses Adsorpsi Mesin Pendingin - Amelia, Septiyan Nur; Sudarsono, Sudarsono; Hasbi, Muhammad (Teknik Mesin Universitas Halu Oleo, 2021)
Indonesia has abundant sources of solar energy with an average solar radiation intensity of about 4.8 kWh/m2 per day throughout Indonesia because it is located at the equator 6°N to 11°N and 9°E-141°E. That way the sun's energy that is not used up can be utilized. The purpose of this study is to determine the heat used by the collector for the desorption process and to determine the effect of variations in the angle of inclination of the collector on the efficiency of the collector. That way, one of them can be used for the water cooling process using a solar collector device on a solar heat adsorption cycle cooling machine The purpose of this study was to determine the heat used by the collector for the desorption process and to determine the effect of variations in the collector tilt angle on the efficiency of the collector. This research was conducted by varying the slope of the cooling machine collector with an adsorption cycle using solar energy. The test results show that the average theoretical useful heat at the collector (Qu) obtained by the 0° angle collector is 236,079 Watt, the 15° angle collector (from 08.00 – 15.30) is 131.683 Watt, and the 30° angle collector (from 08.00 – 16.00) is 179.638 Watt. on each test day. The average efficiency (η) from 08.00 – 15.30 (optimal measurement) obtained by the 0° angle collector is 51.296%, the 15° collector angle is 47.1%, and for the 30° angle collector the average efficiency is from 08.00 – 16.00 (optimal measurement) of 52.836%.Keywords: collector, adsorption, temperature.